The Social Facts of 1982’s Lebanese War in A’tuna Tufuli Song by Remi Bandali: Riffaterre’s Semiotic Analysis - Hermawati Putri Dian Insani (Arabic Literature Department, 2021)
This research aims to reveal the social facts that happened in 1982’s Lebanese War in A'tuna Tufuli’s song by Remi Bandali. This song explains the hope of children who affected by war. It relates to the incident when the song composed, namely the 1982’s Lebanese War between Israel and Palestinian refugees so there are social facts reflected in it. The disclosure of social facts in this research will be analyzed by Semiotic Riffaterre theory. The research method is hereustic and hermeneutic readings to explain the meaning in the lyrics of the song. After that, the meaning of the lyrics will be analyzed by model, variation, matrix and hypogram for every verse of the song to describe how the social facts exist in society. The research shows the data from the lyrics of A’Tuna Tufuli’s song by Remi Bandali is not only a hope for children, but as a reflection of cruelty and chaos of colonialism against society in the 1982’s Lebanese War.